Seafloor images and videos collected along OFOBS profile PS143/1_23-2 during RV POLARSTERN cruise PS143/1 - Lilian Boehringer; Autun Purser; Melanie Bergmann; Tasnuva Ming Khan; Karsten Schimpf; Christopher Krämmer (PANGAEA, 2025)
These images and videos were acquired during the expedition PS143/1 with the German ice breaker FS POLARSTERN in June/July 2024, in the Fram Strait between Greenland and Svalbard. This data supports time-series studies at the LTER (Long-Term Ecological Research) observatory HAUSGARTEN in order to document natural and global change induced environmental variations in polar deep-water ecosystems. The images were acquired by AWIs OFOBS. Aim: Investigation of benthic habitats in the Fram Strait at a target altitude of 1.5 m. Deployment was planned to survey the seafloor along a ridge southeast of HG-I. The laser markers are spaced 50 cm apart.
In: Boehringer, L et al. (2025): Ocean Floor Observation and Bathymetry System (OFOBS) seafloor images and videos of the Fram Strait collected during RV POLARSTERN cruise PS143/1 [dataset publication series]. PANGAEA, https://doi.pangaea.de/10.1594/PANGAEA.987471 (DOI registration in progress)